2011
DOI: 10.1016/j.pocean.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Lower trophic levels and detrital biomass control the Bay of Biscay continental shelf food web: Implications for ecosystem management

Abstract: International audienceThe Bay of Biscay (North-East Atlantic) has long been subjected to intense direct and indirect human activities that lead to the excessive degradation and sometimes overexploitation of natural resources. Fisheries management is gradually moving away from single-species assessments to more holistic, multi-species approaches that better respond to the reality of ecosystem processes. Quantitative modelling methods such as Ecopath with Ecosim can be useful tools for planning, implementing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 82 publications
6
71
0
Order By: Relevance
“…Stergiou and Karpouzi 2002), and specifically in the Bay of Biscay (i.e. data from Ecopath modelling; Lassalle et al 2011). Moreover, this morphological difference would lead anchovies to be opportunistic and efficient planktivores (James and Probyn 1989) on prey species from the mesozooplankton compartment at least and would confirm that E. encrasicolus is not specialist feeder in the Bay of Biscay area, as already reported for the North and Baltic Seas (Raab et al 2011).…”
Section: Linking Resource Variability and Feeding Patterns Of Sardinesupporting
confidence: 53%
See 1 more Smart Citation
“…Stergiou and Karpouzi 2002), and specifically in the Bay of Biscay (i.e. data from Ecopath modelling; Lassalle et al 2011). Moreover, this morphological difference would lead anchovies to be opportunistic and efficient planktivores (James and Probyn 1989) on prey species from the mesozooplankton compartment at least and would confirm that E. encrasicolus is not specialist feeder in the Bay of Biscay area, as already reported for the North and Baltic Seas (Raab et al 2011).…”
Section: Linking Resource Variability and Feeding Patterns Of Sardinesupporting
confidence: 53%
“…In particular, European sardine (Sardina pilchardus) and European anchovy (Engraulis encrasicolus) fisheries are of major importance in the area (ICES 2010a). No quota currently exists for sardine despite an observed decrease in their catches in this area (OSPAR 2010 role in the population dynamics of upper trophic levels and in the global structuring of this marine ecosystem (Lassalle et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…However, in several cases, anchovies are found to feed at a slightly higher trophic level than sardines (e.g., Stergiou and Karpouzi, 2002), and specifically in the Bay of Biscay (i.e., data from Ecopath modelling; Lassalle et al, 2011), which invalidates the first hypothesis.…”
Section: Diet and Feeding Areas Of Small Pelagic Fishmentioning
confidence: 99%
“…Clupeiform fish stocks support an abundant and diverse top predator community in the Bay of Biscay (Lassalle et al, 2011). Our results suggested that competitive relationships can occur between commercial-size meagre and other predator species such as hake and sea bass, two abundant commercial high trophic level fish in European Atlantic waters (Mahé et al, 2007;Spitz et al, 2013), or common dolphin (Meynier et al, 2008), the most abundant cetacean in the Bay of Biscay (Laran et al, 2017).…”
Section: Implications For Eafmentioning
confidence: 69%